Satellite Evidence for Glyoxal Depletion in Elevated Fire Plumes. Issue 4 (24th February 2023) - Lerot, C.; Müller, J.‐F.; Theys, N.; De Smedt, I.; Stavrakou, T.; Van Roozendael, M.
Abstract: Space‐borne observations are used to characterize the fate of formaldehyde and glyoxal in wildfire plumes. Their distribution measured by the Tropospheric Monitoring Instrument reveals striking differences between the two compounds near intense fires. In typical situations, the glyoxal‐to‐formaldehyde ratio is highest near the fire (∼0.1) and decreases downwind of the source area due to the larger contribution of pyrogenic emissions to the glyoxal abundance and to the longer lifetime of formaldehyde. However, a pronounced glyoxal depletion is detected above high‐level clouds, not seen for formaldehyde, likely due to processing in pyrocumulonimbus clouds generated by the fires. This depletion suggests glyoxal retention upon droplet freezing and/or its outgassing in hydrated form in the upper troposphere. The absence of a sizable loss of formaldehyde during convection indicates that its hydration in liquid droplets and subsequent outgassing as methanediol represent at most a minor sink of formaldehyde. Plain Language Summary: Wildfires have a strong impact on air quality and climate owing to their associated large emissions of aerosols and gases. For very intense events, the injected material can reach high altitudes, in particular when the fires induce formation of convective pyrocumulonimbus clouds. Using the high spatial resolution observations from the spaceborne Tropospheric Monitoring Instrument, we investigate the respective distributions of formaldehyde and glyoxal, two proxys for volatile organic compounds emissions, at close proximity of intense fire sources. Typically, the glyoxal signal is maximum near the fire source and decreases downwind, while the formaldehyde distribution is more extended and shows weaker spatial gradient. However, we have identified a significant glyoxal depletion, not seen for formaldehyde, in case of injection at high altitudes, typically above the freezing level, suggesting its retention in ice particles or its outgassing in a hydrated form. Key Points: Space observations of glyoxal‐to‐formaldehyde ratio typically show highest values near fires and decrease downwind A pronounced glyoxal depletion is identified above high‐level pyrocumulonimbus clouds generated by intense wildfires Glyoxal depletion is likely due to retention in ice particles or outgassing as glyoxal hydrate when droplets reach the upper troposphere